Associated cultivated plants in tomato cropping systems structure arthropod communities and increase the Helicoverpa armigera regulation - Dassou, A.G.; Vodouhè, S.D.; Bokonon-Ganta, A.H.; Goergen, Georg E.; Chailleux, A.; Dansi, A.; Carval, D.; Tixier, P. (Cambridge University Press, 2019)
Cultivating plant mixtures is expected to provide a higher productivity and a better control of pests and diseases. The structure of the arthropod community is a major driver of the magnitude of natural pest regulations.